Silicon in Agriculture 2015
DOI: 10.1007/978-94-017-9978-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and Plant–Pathogen Interactions

Abstract: The benefi cial effects of silicon (Si) at preventing plant diseases have been known for many decades, and the list of plant-pathogen interactions infl uenced by Si keeps expanding. However, it is quite evident that the prophylactic properties of Si will vary greatly depending on the plant and the pathogen. The recent discovery of Si-specifi c transporters in rice roots has been instrumental in identifying plants that possessed such transporters and were thus genetically disposed to accumulate Si in their tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Silicon nutrition decreases the incidence and severity of fungal, bacterial and viral diseases, and insect pest infestation in several crop plant species (Ma, 2004;Silva et al, 2010;Zellner et al, 2011;Van Bockhaven et al, 2013;Liang et al, 2015a,b;Reynolds et al, 2016;Sakr, 2016aSakr, ,b, 2017. Most importantly, silicon improved plant resistance against a multitude of stresses without the occurrence of resistance tradeoffs and/or growth and yield penalties (Ma, 2004;Ma and Yamaji, 2006;Epstein, 2009;Van Bockhaven et al, 2013;Liang et al, 2015b). Epstein (1994Epstein ( , 1999Epstein ( , 2009 reported that the absorption of silicon by plants from the soil at differing rates depend on genotype, its concentration in the soil and environmental conditions.…”
Section: Silicon In Plantsmentioning
confidence: 99%
“…Silicon nutrition decreases the incidence and severity of fungal, bacterial and viral diseases, and insect pest infestation in several crop plant species (Ma, 2004;Silva et al, 2010;Zellner et al, 2011;Van Bockhaven et al, 2013;Liang et al, 2015a,b;Reynolds et al, 2016;Sakr, 2016aSakr, ,b, 2017. Most importantly, silicon improved plant resistance against a multitude of stresses without the occurrence of resistance tradeoffs and/or growth and yield penalties (Ma, 2004;Ma and Yamaji, 2006;Epstein, 2009;Van Bockhaven et al, 2013;Liang et al, 2015b). Epstein (1994Epstein ( , 1999Epstein ( , 2009 reported that the absorption of silicon by plants from the soil at differing rates depend on genotype, its concentration in the soil and environmental conditions.…”
Section: Silicon In Plantsmentioning
confidence: 99%
“…It is taken up by plants in an amount exceeding the latter in total, which indicates the most important role of silicon in a living organism. Numerous studies confirm the foregoing [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 58%
“…Silicon has been suggested as a viable option, as it has been shown to improve plant tolerance to various abiotic stresses [30], such as drought [31,32], salinity [33][34][35], heavy metals [36,37], high temperatures [38], freezing conditions [39], and ultraviolet radiation [40,41]. Moreover, silicon has demonstrated efficacy against biological stresses, including fungi, bacteria, and insect pests [42,43]. Previous studies have shown that silicon-treated plants exhibit enhanced resistance to diseases like powdery mildew in both wheat [44] and cucumber [45,46].…”
Section: Introductionmentioning
confidence: 99%